Duplication of the Superior Vena Cava in an Elderly Patient on Hemodialysis - Shu-Hua Chen; Cheng-Jui Lin (International Journal of Gerontology, 2017)
Summary: The prevalence of elderly patients who are dependent on hemodialysis (HD) has increased worldwide. We report the case of an 81-year-old man with end-stage renal disease who displayed a duplication of the superior vena cava (SVC) with bilateral central vein dialysis catheters on chest radiography. Blood gas sampling and chest computed tomography confirmed the abnormality. Communication between the bilateral SVC was observed, and persistent left-sided SVC was drained into the coronary sinus. Although the prevalence of SVC duplication in the general population is extremely rare, SVC duplication can render some difficulty in the placement of a pacemaker or peripherally inserted central catheter. The vascular flow through the catheter from the persistent left-sided SVC was inadequate to support regular HD in our patient. We suggest that early preparation of an arteriovenous (AV) fistula or AV graft is essential for elderly patients with SVC duplication who need long-term HD. Keywords: duplication of the superior vena cava, central vein catheter, hemodialysis, catheter dysfunction, arteriovascular fistula